Preserving and Rehabilitating the Historic Urban Landscape of Istanbul: A Case Study of the Büyükdere District - Özge Ilık Saltık (Iconarp International Journal of Architecture and Planning)
Büyükdere has been a settlement since the Byzantine period and was a popular summer destination for ambassadors and foreigners due to its natural beauty in the 18th and 19th centuries. Nevertheless, while the urban sprawl of Büyükdere continued during the Republican period, the settlement began to lose its cosmopolitan structure. The problematic legal processes of Bosporus caused deterioration in the historical fabric of Büyükdere, even though it was declared a “historical urban site” in 1983.